Soziale Arbeit als Profession Zur Karriere "sozialer Hilfstätigkeit" aus professionssoziologischer Perspektive - Motzke, Katharina (Schriften der KatHo NRW, 2014)
How has social work developed into a scientifically sound practice and how will social work continue to develop as a profession in the future? With this publication, the author for the first time presents a comprehensive reconstruction and socio-historical analysis of the development of social work as a profession in Germany. The sociologically (professionally) sound presentation structures the discourses in the literature on social work in a detailed and unprecedented way. It deals with social work in Germany and its more than 150-year history. Originally conceptualized as a 'social auxiliary activity' (Alice Salomon), social work can be described from a professional sociological perspective as a project for advancement and success, which is rather atypical and in some aspects also ambivalent. Based on the initial processes of the vocationalization of social work, three decisive phases of development were identified from the 1970s onwards. The tracing of this development shows that since its emergence at the beginning of the 20th century, social work has even risen from a semi-profession that was always regarded as deficient to a potential trendsetter for future professional development.